2017
DOI: 10.5897/ajb2017.16090
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Cameroonian bread wheat (Triticum aestivum L.) cultivars revealed by microsatellite markers

Abstract: The assessment of genetic diversity is a key prerequisite for studying the adaptation of populations to new environmental conditions, and therefore for the selection of new varieties. The present investigation aimed to estimate the levels and genetic structure within bread wheat varieties grown in Cameroon. Thus, genetic diversity was assessed in 17 hexaploid wheat cultivars, using 11 microsatellite markers. Genetic resources were collected in the Northwest, Adamawa and North Regions. All pairs of specific mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…A PIC value higher than 0.5 is considered to be a sign of a very informative marker, while 0.5> PIC> 0.25 corresponded to an informative marker (BOTSTEIN et al, 1980). In the present study, the mean PIC value for both types marker was higher than 0.25, comparable to those observed in the study with same type marker (LOPES et al, 2015;SOHAIL et al, 2015), but lower than SSR marker (RAFEIPOUR et al, 2016;HONORE et al, 2017). PIC value is calculated as a maximum of 0.5 when a marker is scored as 50% of 0 and 50% of 1.…”
Section: Resultssupporting
confidence: 88%
“…A PIC value higher than 0.5 is considered to be a sign of a very informative marker, while 0.5> PIC> 0.25 corresponded to an informative marker (BOTSTEIN et al, 1980). In the present study, the mean PIC value for both types marker was higher than 0.25, comparable to those observed in the study with same type marker (LOPES et al, 2015;SOHAIL et al, 2015), but lower than SSR marker (RAFEIPOUR et al, 2016;HONORE et al, 2017). PIC value is calculated as a maximum of 0.5 when a marker is scored as 50% of 0 and 50% of 1.…”
Section: Resultssupporting
confidence: 88%
“…In previous studies, Landjeva et al (2006), reported the PIC values in Bulgarian winter wheat ranged from 0.10 to 0.81, which is confirmed by our study. Salem et al (2014) evaluated 33 diverse bread wheat varieties with Egyptian origin, using 17 SSR markers and the highest and lowest PIC value were 0.75 and 0.59, respectively. Erum et al (2013) reported the average values of 'h' and 'I' as 0.11 and 0.23, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The development of such varieties requires a continuous supply of a source of desirable genes and/or gene complexes. The sources of such genes could be: i) bread wheat varieties, which have not been used very intensively but have a higher general adaptation; ii) landraces; iii) wild relatives; and iv) weed species (Salem & Mattar, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Mexican accessions were obtained via the International Maize and Wheat Improvement Center (CIMMYT), and they included spring accessions from Mexicali and Baja California. The Central African accessions were provided by the Institute of Agricultural Research for Development (IRAD) and farmers (Tekeu et al, 2017). The French accessions were winter lines, and those from North Africa were composed of spring lines acquired from the International Center for Agricultural Research in the Dry Areas (ICARDA).…”
Section: Plant Materialsmentioning
confidence: 99%